Cracking The Code Of Interview Success A Global Classroom Initiative - Zuraina, Ali; Hanisah, Kasbon (UMPSA, 2024)
In an effort to improve student employability, the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), under the initiative of Global Classroom, Centre for Instructional Resources & E-Learning (CIReL), hosted a ground-breaking webinar called “Crafting Your Narrative: Communicative Strategies for Interview Excellence.” More than 60 undergraduate students eager to learn effective interviewing skills attended this insightful workshop presented by Dr. Craig J. Selby, the renowned Academic Director of The Third Degree.